(3TQM GdbUjOI GdefaQLIs - (3RcQjG Hf eMeO Hf CMeO Hf RcQjG GdCfUGQj GdSfjcj GdeUQj GdTGaYqj, CHh jMji , J (B926 (3g` s; (3jhSa Hf eMeO Hf jhSa GdJhRQj , GdJdeSGfj, CHh GdaVd, GHf GdfMhqj,J (B513 (3g` s ((3eMeO Hf eMeO Hf eMeO GdTQhGfi s)
(3ChdgG (B:s
(3bGd GdTjN GdEeGe CHh jMji RcQjG GdCfUGQi GdTGaYi GdMeO ddg GdeaQL ddcQH YbH GdTOI hHYO agPG eG ETJOJ Edjg MGLg GdeJagejf ddefaQLI s
(3BNQgG (B:s
(3aVGFd GdCFeI GdCQHYI cKjQI ePchQg bGd eDAdag Je GdTQM s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH (B14s
(3GdfSNI HgG MhGTs
(3HgG fXGe GdJYbjHIs
(3hfGSN GdeNWhW gh eGdcgG fSNgG dfaSgs
(3hQO ai cTa GdXfhf L(B2 (3U` (B1346 (3Cf GdbUjOI GdefaQLI gi deDda CHh GdaVd jhSa Hf eMeO Hf jhSa GdJhRi GdeJhai SfI (B13 (3g` s
(3bQf GdfSN (B:s
(3GdbQf GdMGOj YTQs
Keywords: (3GdeLGejYs